1989
DOI: 10.1148/radiology.171.1.2928525
|View full text |Cite
|
Sign up to set email alerts
|

Facet joint arthrography in lumbar spondylolysis: anatomic basis for spread of contrast medium.

Abstract: Facet arthrograms in patients with lumbar spondylolyses show spread of contrast medium through pars interarticularis defects into the adjacent ipsilateral facet joint space and across the midline into the contralateral joint space. Transverse and sagittal sections of facet joints from 141 postmortem lumbar spines were studied. Five examples of spondylolysis were found. Anatomic studies of the relationship of the joint recesses to the pars interarticularis demonstrated the basis for the patterns of spread of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 0 publications
2
20
0
2
Order By: Relevance
“…The pars interarticularis normally shields a likely entry site to the retrodural space; communication may also depend on the configuration of the ventral facet joint capsule. 3,8 Adjacent ipsilateral facet joints can also communicate directly through a pars interarticularis defect. 8,9 The supra-adjacent facet has been shown to communicate with a pars defect in 94% of cases; the infraadjacent facet in 63%.…”
Section: Anatomymentioning
confidence: 99%
See 2 more Smart Citations
“…The pars interarticularis normally shields a likely entry site to the retrodural space; communication may also depend on the configuration of the ventral facet joint capsule. 3,8 Adjacent ipsilateral facet joints can also communicate directly through a pars interarticularis defect. 8,9 The supra-adjacent facet has been shown to communicate with a pars defect in 94% of cases; the infraadjacent facet in 63%.…”
Section: Anatomymentioning
confidence: 99%
“…3,8 Adjacent ipsilateral facet joints can also communicate directly through a pars interarticularis defect. 8,9 The supra-adjacent facet has been shown to communicate with a pars defect in 94% of cases; the infraadjacent facet in 63%. 9 This anatomy provides the potential for involvement of the posterior ligamentous complex of vertically adjacent spinal segments.…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…Periarticular corticosteroid injection may offer the same therapeutic benefits as intra-articular corticosteroid administration (31,128). Document the extra-articular leak of contrast material into a synovial cyst, intraligamentous cavity, or retrodural space (125,126,129). At lumbar levels, synovial cyst rupture is feasible by placing the needle into the facet joint with fluoroscopic guidance or directly into the cyst or facet joint with CT guidance (Fig 7).…”
Section: Resultsmentioning
confidence: 99%
“…Radiologists recognise that there are connections between a facet joint and a nearby spondylolytic defect, but this does not appear to have been reported by surgeons. 11 reported that the spondylolyses in five young male cadavers "resembled osteoarthritic joints": three were lined by sclerotic bone or cartilage, with the fragments separated by a clear space, and two were joined by fibrocartilage. In all five the pseudarthrosis communicated with the facet joint above and in three also with the joint below.…”
Section: Discussionmentioning
confidence: 99%